Effective Adsorption of Phenoxyacetic Herbicides by Tomato Stem-Derived Activated Carbons - Krzysztof Kuśmierek; Beata Doczekalska; Maciej Sydor; Andrzej Świątkowski (Applied Sciences)
Six activated carbons from tomato (Solanum lycopersicum L.) stems (TS-AC) were synthesized by carbonization and chemical activation using potassium hydroxide (KOH) and sodium hydroxide (NaOH) at temperatures of 550, 650, and 750 °C. These TS-ACs were then evaluated as adsorbents to remove 2,4-dichlorophenoxyacetic acid (2,4-D) and 2-methyl-4-chlorophenoxyacetic acid (MCPA) from aqueous solutions. The adsorption kinetics of both herbicides followed the pseudo-second-order model, closely correlating with the mesopore volume of the TS-AC. The Langmuir isotherm accurately described the adsorption process for both 2,4-D and MCPA. The porous structure of TS-AC, characterized by micropore volume and specific surface area, significantly influenced the maximum adsorption capacities. The adsorption of both herbicides was pH dependent, but ionic strength had no significant effect. Regeneration testing, conducted over three cycles, showed less than a 15% reduction in herbicide adsorption capacity. This study demonstrates that agricultural waste, specifically tomato stems, can be effectively valorized by using simple activation techniques in TS-AC that are efficient adsorbents to remove organic pollutants, such as herbicides, from aqueous media.